Fliers in Peru (18th and 19th centuries) - Cornejo Quesada, Carlos (2012)
After mid-eighteenth century the Viceroyalty of Peru began a series of administrative reforms in an effort to streamline the needs of the Spanish BourbonMonarchy. These reforms affected different social sectors, mainly “criollos”, “mestizos” and indians. This will bring with it a series of protests and rebellions, many of which were expressed, among others, in anonymous Fliers against the Spanish Authorities, unlike the official newspapers that do not meet characterized by malaise and social rebellions that spread in Upper and Lower Peru until the early nineteenth century.